2008
DOI: 10.1038/oby.2008.208
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Overweight and Obesity in Chinese Adults: Between 1991 and 1999–2000

Abstract: Objective: The aim of this study was to evaluate trends in BMI and the prevalence of overweight (BMI ≥ 25 kg/m 2 ) and obesity (BMI ≥ 30 kg/m 2 ) between 1991 and 1999-2000 among Chinese adults. Methods and Procedures: In this study, two population-based samples of Chinese adults aged between 45 and 79 years (n = 7,858 during each period), and comparable in the distributions of age, gender, degree of urbanization, and region (North/South) were used. Height and weight were measured using identical procedures at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
42
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 25 publications
6
42
1
Order By: Relevance
“…These prevalence rates are higher than the rate reported in other Chinese study (Wildman et al 2008) and lower than the reported rate in the US (Flegal et al 2010). Among this sample, the average of BMI slightly increased from 23.2 kg/m 2 in 1997 to 23.9 kg/m 2 in 2006.…”
Section: Discussioncontrasting
confidence: 54%
“…These prevalence rates are higher than the rate reported in other Chinese study (Wildman et al 2008) and lower than the reported rate in the US (Flegal et al 2010). Among this sample, the average of BMI slightly increased from 23.2 kg/m 2 in 1997 to 23.9 kg/m 2 in 2006.…”
Section: Discussioncontrasting
confidence: 54%
“…15 Moreover, climate, lifestyle, diet, and obesity rates are different between various regions in China. 23,24 Even defining urbanicity is challenging given the multifarious features of urbanization in China. A determination of how each of the features of urbanization may influence disease susceptibility has not yet been done.…”
Section: ' Chinese Urbanization and Health: Complex Relationships?mentioning
confidence: 99%
“…7,8 With the continuing increases in general well-being and standard of living, it is expected that the problem of obesity will further increase. 9 Although obesity has been shown to be associated with an increased risk of cardiovascular diseases and diabetes, [10][11][12][13] it is not yet clear whether the increased prevalence of obesity in the Taiwanese population in the last 30 years is reflected by increased risk of chronic disease. Because of rapid economic and population growth, the living environment (for example affordability and availability of food, transportation, housing) has been transformed dramatically, and the mismatch between foetal programming and the subsequent environment may therefore cause health problems in later life.…”
Section: Introductionmentioning
confidence: 99%